Impact of smartphone use on health among higher secondary level students in Khulna, Bangladesh - Chowdhury, S; Basu, BK; Laskar, MS (Mediscope, 2018)
Smartphone is used worldwide even by students as a very much necessary electronic device. The present study aimed at finding out any impact of smartphone use on health of higher secondary certificate level students in Khulna, Bangladesh using a semi-structured questionnaire, which included different socioeconomic characteristics such as social status, duration of smartphone use, related possible health problems like eye strain, headache, hearing problem, sleep disturbance and depression. Three hundred seventy students participated in this study. The modes of using smartphone by the students were: no use, audio calls, video calls, gamming, chatting, facebooking, and taking photo. The students were 40.5% of 11th level and 59.5% of 12th level, 42.2% of age <17 years, 43.8% males, 76.8% came from urban schools, 84.9% with science background, 35.7% had family members >4, 65.1% had parents with higher social status, 89.7% used smartphone, and 34.6% used with daily duration >1 hour. The smartphone use was significantly associated with sleep disturbance (p < 0.05) as an expression of health impact. The symptom sleep disturbance significantly associated with other reported symptoms by the respondents like eye strain, headache, hearing problem, and depression. All the symptoms were positively and significantly inter-related (p < 0.05 or p < 0.01). Smartphone should be used with a cautious manner, as there might be a chance to develop health related symptoms Mediscope Vol. 6, No. 1: Jan 2019, Page 1-5